ANALISIS SIMULASI PENGARUH UJI KUAT SINYAL WIFI DARI BAHAN-BAHAN OBSTACLE - M Hanafi . (Faculty of Engineering, Universitas Tanjungpura, 2019)
Wifi networks Analizer is a software that can measure the signal strength received by a mobile phone so that it can see the signal strength that will be examined by looking at the signal quality scale of <-60 dBm with very good quality, -61 dBm to -70 dBm in good category, -71 dBm to -80 dBm with pretty bad quality, -8 1 dBm to -90 dBm with poor signal quality, and> -91 dBm signal quality shows very bad. For testing the wifi signal strength, the router and cellphone must be connected first, after connecting, then measuring the distance that has been determined by the tester, for the first test the Wifi router is not given a barrier to become a measurement barometer, after that it is measured with a barrier that has been determined by the distances that have been measured, so that another value can occur due to the barrier given to the Wifi router. From this research can be explained that there is a reduction in the wifi signal strength against the barrier given with different values on each barrier, and the influence of distance measurement also affects the quality of the network where to measure a distance of 5 meters to 15 meters is still in good quality, whereas with a distance of 20 meters to 30 meters signal quality is obtained with an average yield between - average for 70.33 dBm without barrier, 72.66 dBm plywood box, 76.33dBm concrete box and 75.66dBm ceramic box, when compared to the table RSSI indicator then the results can be quite bad.